PERSPEKTIF DAN EVALUASI GURU DAN SISWA MENGENAI KURIKULUM PENDIDIKAN AGAMA KRISTEN - Santi Santi; Santi Mongan, Martina Suli', Diana Pakurung, Anugrawati Sarira (CV. ADIBA AISHA AMIRA, 2024)
This research aims to explore and analyze the perspectives and evaluations of teachers and students regarding the Curriculum of Christian Religious Education at the secondary education level. The research focuses on teachers' views on the diversity of materials, teaching methods, and the curriculum's relevance to students' daily lives. Meanwhile, students are assessed from the perspective of the diversity of learning approaches, the attractiveness of the material, and the curriculum's ability to shape a profound understanding of Christian religious teachings. The research methodology employed is a qualitative approach with in-depth interview techniques conducted with a number of PAK teachers and secondary-level students. Thematic data analysis is conducted to identify common patterns and diflerences in the perspectives and evaluations of both groups regarding the curriculum. The expected outcome of this research is to provide a comprehensive overview of the successes and challenges in the implementation of the Curriculum of Christian Religious Education, with the potential to contribute to curriculum improvement and the development of more eflective teaching practices. The implications of this research may also support policy-making eflorts to enhance the quality of Christian religious education at the secondary level.